Moderately Prolonged QTc in Computer-Assessed ECG, Random Variation or Significant Risk Factor? A Literature Review - Jan Hysing; Charlotte Gibbs; Øystein Lunde Holla; Jacob Thalamus; Kristina H. Haugaa (Cardiogenetics, 2022)
Most ECGs in European hospitals are recorded with equipment giving computer measured intervals and interpretation of the recording. In addition to measurements of interval and QRS axis, this interpretation frequently provides the Bazett’s-corrected QTc time. The introduction of computer-corrected QTc revealed QTc prolongation to be a frequent condition among medical patients. Nevertheless, the finding is frequently overlooked by the treating physician. The authors combine experience from a local hospital with a review of the current literature in this field in order to elucidate the importance of this risk factor both as congenital long QT syndrome and as acquired QT prolongation.